Analisis Variasi Spasial a- dan b-Value Sebagai Indikator Kegempaan di Wilayah Nusa Tenggara bagian Timur - Rahmadani, Putri Amindar; Risky Martin Antosia; Anas Fauzi Masykuri; Putu Pradnya Andika (Mataram University, 2025)
Eastern Nusa Tenggara, encompassing Timor, Flores, Alor, and Kupang City, lies along the active collision zone between the Indo-Australian and Eurasian plates, making the region highly susceptible to earthquakes. This study analyzes the spatial variation of a-value and b-value based on the earthquake catalog from 1998–2023 using ZMAP v.6.0 software. The frequency–magnitude distribution (FMD) curve indicates an inverse relationship between earthquake frequency and magnitude. Spatially, relatively high b-values are observed in eastern Flores to Alor, indicating frequent seismic activity with low released energy, while the variation of a-value reflects the level of seismicity, ranging from 5.0–6.0, with b-values between 0.8–1.1. These findings provide valuable insights for disaster mitigation, infrastructure planning, and enhancing community preparedness in Eastern Nusa Tenggara, including Kupang City.